Assembling ZnO Nanorods into Microflowers through a Facile Solution Strategy: Morphology Control and Cathodoluminescence Properties - Lei, Ying; Qu, Fengyu; Wu, Xiang (Nano-Micro Letters, 2012)
In this work, flowerlike ZnO micro/nanostructures assembled from nanorods are obtained through a facile hydrothermal route. The experimental results indicated that the as-synthesized ZnO microflowers have an average diameter of 2 µm, composed of nanorods of an average diameter of 200 nm and a tapered morphology. ZnO with other morphologies were also obtained by varying the reaction conditions. Systematical condition-dependent experiments were conducted to reveal the growth mechansim of the microflowers. It is suggested that the zinc source types, solution pH value, and reaction temperature, as well as reaction time are responsible for the variations of ZnO morphology. Luminescence properties of ZnO microflowers were investigated through monitoring different parts of nanorods, showing good optical quality.